EVALUATING DATA SOURCES IN ACADEMIC RESEARCH - Kandaxarova Diyora (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In modern academic research, evaluating data sources has become an essential skill for students and researchers. The rapid growth of digital information has made access to knowledge easier, yet it has also increased the risk of using unreliable or biased materials. This article discusses the importance of evaluating academic sources, presents key evaluation criteria such as credibility, relevance, and accuracy, and examines common challenges faced during research. The study highlights the role of critical thinking in selecting high-quality academic information.